Implementasi Digitalisasi Pendidikan Untuk Meningkatkan Sikap Toleransi Siswa Dalam Perspektif Aswaja - Maula Nurul Inaya; Ahmad Khori; Fitri Nopyanti; Nuniek Prahesti Wijayanti (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
This study aims to analyze the implementation of educational digitalization in strengthening students’ tolerance attitudes from the perspective of Ahlussunnah wal Jama’ah (Aswaja) at SMP Al-Amanah, Bandung Regency. The research employed a qualitative approach using a case study design. Data were collected through observations, semi-structured in-depth interviews, and documentation involving the principal, teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure data validity. The findings indicate that educational digitalization implemented through a blended learning model contributes positively to strengthening students’ tolerance attitudes. The integration of Aswaja values—tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and ta’adul (justice)—is reflected in learning materials, digital learning activities, and student interactions. Students demonstrate increased ability to accept differences, communicate respectfully, and exhibit inclusive attitudes in digital and face-to-face learning contexts. The successful implementation is supported by teachers’ roles, school leadership, and a conducive school culture, although challenges remain in the form of limited digital literacy and unequal access to technology. This study highlights that value-based educational digitalization plays a strategic role in fostering tolerant student character in the digital era